Simultaneous Quantitation of Three Aromatic Compounds by Fluorescence Spectroscopy and Elastic Component Regression. (13th April 2017) - Wu, Tong; Chen, Hui; Lin, Zan; Tan, Chao
ABSTRACT: The determination of aromatic compounds is of importance in many fields. Even if these compounds may be determined by molecular fluorescence and second-order calibration, the methods are relatively complex and require higher mathematics. Here is explored whether the reduction of the dimensions, i.e., transforming two-dimensional data to one-dimensional data followed by a special variable selection and calibration process, is feasible for this purpose. The present work investigated the feasibility of combining competitive adaptive reweighted sampling and elastic component regression for the direct evaluation of the spectra to quantify three components simultaneously. Model population analysis has also been performed. The results confirmed the feasibility of the procedure, which may serve as an alternative method to simultaneously determine aromatics.